Investor Tax Credits and Entrepreneurship: Evidence from U.S. States - DENES, MATTHEW; HOWELL, SABRINA T.; MEZZANOTTI, FILIPPO; WANG, XINXIN; XU, TING (Journal of Finance, 2023)
ABSTRACT Angel investor tax credits are used globally to spur high‐growth entrepreneurship. Exploiting their staggered implementation in 31 U.S. states, we find that they increase angel investment yet have no significant impact on entrepreneurial activity. Two mechanisms explain these results: crowding out of alternative financing and low sensitivity of professional investors to tax credits. With a large‐scale survey and a stylized model, we show that low responsiveness among professional angels may reflect the fat‐tailed return distributions that characterize high‐growth startups. The results contrast with evidence that direct subsidies to firms have positive effects, raising concerns about promoting entrepreneurship with investor subsidies.